A Toxicogenomic Comparison of Primary and Photochemically Altered Air Pollutant Mixtures - Rager, Julia E. (National Institute of Environmental Health Sciences, 2011)
Background: Air pollution contributes significantly to global increases in mortality, particularly within urban environments. Limited knowledge exists on the mechanisms underlying health effects resulting from exposure to pollutant mixtures similar to those occurring in ambient air. In order to clarify the mechanisms underlying exposure effects, toxicogenomic analyses are used to evaluate genomewide transcript responses and map these responses to molecular networks. Objectives: We compared responses induced by exposure to primary pollutants and photochemically altered (PCA) pollutant mixtures representing urban atmospheres to test our hypothesis that exposures to PCA pollutants would show increased modulation of inflammation-associated genes and pathways relative to primary air pollutants. Methods: We used an outdoor environmental irradiation chamber to expose human lung epithelial cells to mixtures representing either primary or PCA pollutants for 4 hr. Transcriptional changes were assessed using microarrays and confirmed using quantitative real-time reverse-transcription polymerase chain reaction (qRT-PCR) on a subset of genes. Results: We found a large difference in the cellular responses to the two pollutant exposures: Primary air pollutants altered the expression levels of 19 genes, whereas PCA pollutants altered 709 genes. Functional and molecular analyses of the altered genes revealed novel pathways, such as hepatocyte nuclear factor 4α, potentially regulating the pollutant responses. Chemical component analysis characterized and confirmed the photochemical transformation of primary air pollutants into PCA air pollutants. Conclusions: Our study shows that the photochemical transformation of primary air pollutants produces altered mixtures that cause significantly greater biological effects than the primary pollutants themselves. These findings suggest that studying individual air pollutants or primary pollutant mixtures may greatly underestimate the adverse health effects caused by air pollution.